Organizational legal principles of creation of poltava land bank in the context of its practical activity (1872-1917) - Селіхов, Д. А. (Problems of legality, 2013)
The Charter of Poltava Land Bank has been analyzed in the article in the terms of characteristics of its organizational legal activity at the turn of the XIX-XX centuries. Some economic results of this bank have also been elucidated against the background of other land banks which functioned at the appointed time in Poltava Region.